Recent advances on Hippo-YAP pathway in skin diseases - Cai, Xuxia; Chen, Kexin; Li, Xiahong; Zhang, Kaoyuan; Gu, Jiaxu; Shen, Changbing; Yu, Bo; Huang, Cong (Frontiers in Immunology, 2026)
The Hippo-YAP pathway is a critical signaling cascade that regulates essential cellular processes, including proliferation, inflammation, and the fate of cancer cells. Recent studies have increasingly highlighted the significant role of the Hippo-YAP pathway in the pathogenesis and progression of various skin diseases. This review aims to summarize the latest advancements related to the Hippo-YAP pathway in skin disorders, exploring its regulatory mechanisms in the context of skin tumors, inflammatory skin diseases, skin aging, wound healing and skin development. Furthermore, this review will analyze the current challenges and knowledge gaps within this field and propose future directions and potential therapeutics targeting the Hippo-YAP pathway to improve treatment outcomes for skin diseases. This review also acknowledges several limitations, including the heterogeneity of existing studies, variations in experimental models, and the scarcity of clinical evidence directly linking Hippo-YAP dysregulation to specific skin diseases. These factors highlight the need for more standardized and clinically oriented research in the future.